SAT0193 THE USE OF A SYMPTOM CHECKLIST TO RECOGNISE PATIENTS WITH COMORBID FIBROMYALGIA ON A BACKGROUND OF SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Huang, Frank; O'neill, Sean; Fang, Ray; Nguyen, Matthew; Gibson, Kathryn
Abstract : Background: Fibromyalgia (FM) and systemic lupus erythematosus (SLE) are both characterised by non-specific symptoms such as pain and fatigue. To make diagnosis even more challenging, fibromyalgia is overrepresented in the SLE population. Objectives: To identify which symptoms can discriminate between patients with comorbid FM and patients without comorbid FM in the SLE population, using a routinely distributed questionnaire. Methods: Patients with SLE (n=88) completed a Multi-Dimensional Health Assessment Questionnaire (MDHAQ) [1] and the 2011 FM Criteria questionnaire [2]. FM status was determined using the 2016 modification of the 2010/2011 FM criteria [3]. The MDHAQ contains a 60-item symptom checklist section, giving a score of 0-60. Patients with complete data were analysed for specific symptoms that were discriminating for FM using student's t test with Bonferroni correction. Results: SLE patients with FM reported a higher prevalence of positive responses for every symptom except for 'dark or bloody stools' and 'burning in sexual organs'. Nineteen symptoms demonstrated a significant difference between those with and without FM. The most discriminating symptoms were muscle pain, swelling (of hands, ankles and in other joints), back pain, neck pain, problems with thinking and dry mouth (all p <0.0001). Grouping the above 8 symptoms, a cut-off of ≥4 gave a sensitivity of 91% and specificity of 88%, correctly classifying 89% of patients when compared to FM criteria. Overall, patients with FM reported a mean total of 23.6 items on the symptom checklist, compared to 8.09 for patients without FM. Conclusion: The symptom checklist section of the MDHAQ can provide clues that help discriminate between SLE patients with and without FM. Clinicians can find valuable information in the specific symptoms experienced by the patient, as well as the overall number of symptoms. Grouping the discriminatory symptoms together in the questionnaire may assist clinicians to consider the diagnosis of FM more easily in patients with SLE. References: [1] Pincus, T., Y. Yazici, and M. Bergman, Development of a multi-dimensional health assessment questionnaire (MDHAQ) for the infrastructure of standard clinical care. Clinical & Experimental Rheumatology, 2005. 23(5Suppl 39): p.S19-28. [2] Wolfe, F., et al., Fibromyalgia criteria and severity scales for clinical and epidemiological studies: a modification of the ACR Preliminary Diagnostic Criteria for Fibromyalgia. J Rheumatol, 2011. 38(6): p.1113-22. [3] Wolfe, F., et al. 2016Revisions to the 2010/2011 fibromyalgia diagnostic criteria. in Seminars in arthritis and rheumatism. 2016. Elsevier. Disclosure of Interests: Frank Huang: None declared, Sean O'Neill: None declared, Ray Fang: None declared, Matthew Nguyen: None declared, Kathryn Gibson Grant/research support from: UCB, Abbvie, Speakers bureau: UCB, Janssen